Exciton–polariton formation at room temperature in a planar ZnO resonator structure - Schmidt-Grund, R.; Rheinländer, B.; Czekalla, C.; Benndorf, G.; Hochmuth, H.; Lorenz, M.; Grundmann, M. (Applied physics. B, Lasers and optics, 2008)
We show the dispersion of exciton–polaritons in an all oxide planar resonator structure. A quasi-bulk ZnO film acts as active medium and as cavity. The mirrors are made of Bragg reflectors consisting of ZrO 2 and MgO layers. Despite a limited structural perfection, we have observed a giant energy splitting of the exciton–polariton branches of about 78 meV at maximum using reflectivity and photoluminescence measurements.